Nanozyme Based on Porphyrinic Metal–Organic Framework for Electrocatalytic CO2 Reduction. Issue 1 (9th January 2023) - Lee, Junghye; Choi, Hansaem; Mun, Jinhong; Jin, Eunji; Lee, Soochan; Nam, Joohan; Umer, Muhammad; Cho, Jaeheung; Lee, Geunsik; Kwon, Youngkook; Choe, Wonyoung
Abstract : Nanozyme Based on Porphyrinic Metal‐Organic Frameworks A new 2D porphyrin‐based metal‐organic framework is constructed from a highly nonplanar saddle‐distorted porphyrin linker to mimic a natural enzyme system. In article number 2200087, Wonyoung Choe, Youngkook Kwon, Geunsik Lee, and co‐workers present a new synthetic strategy to mimic the active center and tunes the secondary coordination sphere are improved to both effective CO2 catalyst system.